(1204) Industrialization and organization in Hungarian agriculture التصنيع والتنظيم في الزراعة المجرية - fekete, fereng (معهد التخطيط القومى, 2020)
The present paper surveys the new phenomena accurred in course of the last on-and-a-half decades within the development of Hungarian agriculture concerning many aspects